1997
DOI: 10.1152/ajpendo.1997.272.3.e437
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of gluconeogenesis by glutamine in normal postabsorptive humans

Abstract: There is evidence that glutamine may act as a regulator of protein, free fatty acid, and glycogen metabolism. To test the hypothesis that glutamine may act as a physiological regulator of gluconeogenesis, we infused 16 normal postabsorptive volunteers with glutamine at a rate (11.4 micromol kg(-1) x min(-1)) estimated to approximate its appearance in plasma after a protein meal and assessed changes in production of glucose from glutamine, systemic glucose appearance and disposal, and uptake and release of gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…This has been shown using intravenous lactate [70,102,103] alanine [68,104], glutamine [69], glycerol [68,71,105], and fructose [35] (Table 3).…”
Section: Intravenous Infusion Of Gluconeogenic Substratesmentioning
confidence: 77%
See 2 more Smart Citations
“…This has been shown using intravenous lactate [70,102,103] alanine [68,104], glutamine [69], glycerol [68,71,105], and fructose [35] (Table 3).…”
Section: Intravenous Infusion Of Gluconeogenic Substratesmentioning
confidence: 77%
“…However, several studies using different gluconeogenic substrates such as amino acids, lactate, glycerol and the monosaccharides, fructose and galactose, have shown that there is little change in glucose production in the post-absorptive state, despite increased availability of substrates [68][69][70][71][72][73].…”
Section: Regulation Of Gluconeogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Glutamine is synthesized from amination of glutamate via glutamine synthetase and catabolized via deamination back to glutamate via glutaminase. Glutamine carbon enters the TCA cycle as ␣-ketoglutarate and is used for energy or for formation of new glucose (28). Glutamate itself can be used as precursor for glutathione, the major intracellular anti-oxidant.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, I also reestablished my long-standing collaboration with Jack Gerich in a series of experiments demonstrating how the enhanced information content available in studies employing both stable-and radio-tracer-labeled gluconeogenic substrates results in a more comprehensive understanding of the gluconeogenic process in humans (36,37,119,129,130,147).…”
Section: Adults Are Just Big Kidsmentioning
confidence: 97%